Social Exclusion and Employment: ¿What Happen If Labor Market Segmentation Exists? - Pedraza Avella, Aura Cecilia (Sociedad y Economía, 2012)
Employment has been traditionally considered the best action against social exclusion, but in this research is showed there is no evidence that employed or unemployed are mainly excluded in Colombia. Instead, analyzing the differences between social exclusion of workers depending on their participation in any segment of the labor market, it is proved that the best quality of employment in the primary segment influences the lower exclusion of its workers compared to those of the secondary segment whose disadvantage is similar to the unemployed portion of the labor market. It is found too that measuring social exclusion, including labor market segmentation is better than doing it using unemployment as the unique indicator of disadvantage in the labor market.